Servants or Masters? Linguistic Aids in Legal Interpretation - Paulina Konca (Universidad Hemisferios, 2021)
This paper presents the role of some intrinsic sources in legal interpretation. Some of linguistic aids follow from provisions of the law and other from the commonly accepted ruling practice or views expressed in literature. The position of those aids was verified through the analysis of case-law, literature, and provisions of law. The first section and second section focus on the priority of plain meaning rule and intrinsic sources in legal interpretation which is strongly emphasized in legal literature, case-law and the interpretative provisions of many countries. Next, it presents how certain linguistic tools work in case law practice, what problems they can cause and what problems they can solve. The third point addresses the use of dictionaries as tools of linguistic interpretation. The fourth section explores the role of selected interpretative canons often found in legal regulations and case law practice: ordinary meaning canon, gender/number canon, ejusdem generis canon, presumption of consistent usage and prefatory-materials canon. It is concluded that the priority of a linguistic interpretation is not absolute and can never be understood as its exclusivity. Linguistic tools are not in themselves determinants of correct meaning. In order to make a correct interpretation, it is necessary not to be guided, by indications labelled as objective, sometimes artificially imposed, but by the intention of the legislator, which such tools may discover and should only be used for that purpose.